2018
DOI: 10.1159/000490794
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Particle Size in Free-Ranging Proboscis Monkeys, Nasalis larvatus: Variation between Seasons

Abstract: Reducing the size of food particles is crucial for herbivores. Seasonal dietary changes are known to influence animals’ chewing efficiency. Proboscis monkeys (Nasalis larvatus) are foregut fermenters, with a high chewing efficiency allowing them to achieve very fine faecal particles. In this study, we investigated how proboscis monkeys’ chewing efficiency varies between wet and dry seasons, hypothesising differences possibly related to diet change. Faecal particle size analysis is an established approach to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…These authors hypothesized that the mainly frugivorous diet may be mechanically less challenging compared to the more folivorous diet of geladas. Likewise, Milette, Sauther, Cuozzo, and Ness () suggested for ring‐tailed lemurs ( Lemur catta ) that fruits are easier to process and digest than leaves, and Thiry et al () found that proboscis monkeys ( Nasalis larvatus ) had smaller FPS during the wet season when their feces contained higher amounts of seeds, indicating frugivory.…”
Section: Introductionmentioning
confidence: 99%
“…These authors hypothesized that the mainly frugivorous diet may be mechanically less challenging compared to the more folivorous diet of geladas. Likewise, Milette, Sauther, Cuozzo, and Ness () suggested for ring‐tailed lemurs ( Lemur catta ) that fruits are easier to process and digest than leaves, and Thiry et al () found that proboscis monkeys ( Nasalis larvatus ) had smaller FPS during the wet season when their feces contained higher amounts of seeds, indicating frugivory.…”
Section: Introductionmentioning
confidence: 99%
“…Base on the hypothesis that dietary toughness impedes chewing (Pérez-Barbería & Gordon, 1998;Venkataraman et al, 2014), we predicted that fecal particle size increases when dietary toughness increases. A previous study found smaller fecal particle sizes when proboscis monkeys consumed preferred food (Thiry et al, 2018). We predicted that higher fruit consumption leads to smaller fecal particle size, while higher mature leaf consumption results in larger fecal particle size.…”
Section: Introductionmentioning
confidence: 74%
“…Since the digestion processes other than mastication have little influence on digesta particle size in terrestrial mammalian herbivores (McLeod & Minson, 1988b;Poppi et al, 1980;Spalinger & Robbins, 1992), fecal particle size has been repeatedly used as a proxy for chewing efficiency (Dunbar & Bose, 1991;Fritz et al, 2009;Matsuda et al, 2014;Venkataraman et al, 2014;Weary et al, 2017). Previous studies have found that several factors affect fecal particle sizes in different primate species, such as diet composition (Thiry et al, 2018;Weary et al, 2017), dietary toughness and age (Venkataraman et al, 2014), and re-mastication (Matsuda et al, 2014). However, some of these factors only pertained to species with a highly specialized lifestyle (Matsuda et al, 2014;Venkataraman et al, 2014), while the determinants of fecal particle size remain unclear in other species (He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wild, the breeding season for proboscis monkeys could be affected by the rainfall pattern altering the abundance of leaves which give nutrients, consequently affecting chewing efficiency and rumination ( 27 ). It is logical to investigate the environmental impact on the breeding season of the proboscis monkey.…”
Section: Discussionmentioning
confidence: 99%